The evolutionary development in drug discovery and delivery - Ithnin, Hairuszah; Hussein, Mohd. Zobir; Tan, Julia Meihua; Fakurazi, Sharida (Elsevier, 2013)
To investigate what a drug delivery system is and the way it changes the modern pharmaceutical industry of today, a review of the historical background of drug discovery and the pharmaceutical development of drug delivery in ancient times is necessary. This armamentarium serves as a novel input for medicinal chemists to advance drug design and move development into another magnitude, as most modern medicines of today are based on conventional medicines of the past. This paper mainly highlights the melodrama of drug transformation, from discovery to delivery, enabling a better understanding of the various issues involved in the drug development process of the past with the aim of developing novel targeted drug delivery systems in the near future. In addition, the primary applications of different forms for drug delivery routes are also discussed and exemplified here as well as the major barriers faced by pharmaceutical companies relative to their drug development projects.